The Diagnostic and Management of Drug Induced Esophagitis - Alkindi Bahar; Ari Fahrial Syam; Chudahman Manan (The Indonesian Society for Digestive Endoscopy, 2002)
There are several factors that involve in drug induced esophagitis such as: drugs, esophagus, patients. The drug can cause direct effect to the esophageal mucosa. The drugs that often cause esphagitis: alendronate, tetracycline and its derivates and anti retroviral agents. Most of these drugs can cause esophageal damage due to corrosive nature of the drug. Esophageal factor that can cause the drug induced esophagitis: rheumatic heart disease, enlargement of the left atrium mass and aortal aneorysma. These conditions will disturb drug passage and prolongs drug contact with esophageal mucosa. The patients factor that influences this problem is the patients position when taking the drug, the patients age, the amount of water taken along with the drug, the time when drug was taken, and the amount of saliva. Endoscopy is a good procedure to evaluate the esophageal mucosa and establishing differential diagnosis through direct inspection, biopsy. In the management of esophagitis, PPIs are currently the most effectiveness agents available for treating esophagitis. Esomeprazole, an optical isomer of omeprazole is the first PPI to show greater efficacy than other PPI is in esophagitis healing. Keywords: Esophagitis, drug induced, proton pump inhibitor.